2015
DOI: 10.1139/cjc-2014-0426
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mycobacterial activities of copper(II) complexes. Part II. Lipophilic hydroxypyridinones derived from maltol

Abstract: Eight lipophilic 3-hydroxy-4-pyridinones have been prepared from a microwave-mediated reaction along with the corresponding copper(II) complexes. All complexes have been obtained elementally pure and X-ray diffraction studies on two of the copper complexes have confirmed the structure of these compounds. Some of these complexes showed a promising degree of anti-mycobacterial activity against Mycobacterium tuberculosis, where activity seemed to vary by substitution at the pyridinone nitrogen atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Salsbury et al13 showed that copper(II) complexes containing lipophilic hydroxypyridinone-derived ligands (2a and 2h) exhibited considerable antimicrobial activity against M. tuberculosis H 37 R a with a minimum inhibitory concentration (MIC) of 12.50 μg/mL for both complexes. In addition, Hoffman et al14 demonstrated that copper(II) pyrophosphate complexes [Cu(phen)(H 2 O)(H 2 P 2 O 7 )] (phen =1,10′-phenanthroline) showed promising antimicrobial activity against M. tuberculosis H 37 R v with an MIC of 31.25 μg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Salsbury et al13 showed that copper(II) complexes containing lipophilic hydroxypyridinone-derived ligands (2a and 2h) exhibited considerable antimicrobial activity against M. tuberculosis H 37 R a with a minimum inhibitory concentration (MIC) of 12.50 μg/mL for both complexes. In addition, Hoffman et al14 demonstrated that copper(II) pyrophosphate complexes [Cu(phen)(H 2 O)(H 2 P 2 O 7 )] (phen =1,10′-phenanthroline) showed promising antimicrobial activity against M. tuberculosis H 37 R v with an MIC of 31.25 μg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…A panel of probes was prepared where the Phe-residue in the tetrapeptide sequence central part (18,(21)(22), at the nitrogen-terminus (19) or the carbon-terminal lysine (20) was replaced by the dual fluorescent probe. A structural analog of 20 was represented by compound 23, where a protected Fechelating moiety (17) was incorporated into the structure. Compounds 26 and 27 were designed by the activation of the glutamic acid residue, which was orthogonally protected on the solid support for the selective conjugation of either 1°- (24) or 2°-amine (25) having HOPO (Fig.…”
Section: Sensing Of Iron In Living Systemsmentioning
confidence: 99%
“…[9 -12] Ethyl maltol (1, 2-ethyl-3-hydroxy-4H-pyran-4-one, Figure 1) is the analog of maltol (I, 2-methyl-3-hydroxy-4H-pyran-4-one, Figure 1) and have similar biological activities to maltol. Maltol, a commercial natural metabolite, is primarily extracted from germinated seeds of Hordeum vulgare L. and Triticum aestivum L. [13] To the best of our knowledge, maltol is an excellent candidate for the study of antifungal activity, [14] anticancer activity, [15] anti-mycobacterial activity, [16] antioxidant activity, [17] neuroprotective effect, [18] and liver protection effect. [19] Moreover, maltol is used extensively as a food preservative, flavor-enhancing agent, and also in pharmaceutical and cosmetic formulations.…”
Section: Introductionmentioning
confidence: 99%